GAMBARAN PERMA PADA LANSIA YANG MELAKSANAKAN KEGIATAN HORTIKULTURA - Victoria Alexandra Aureli Prasetyo; Riana Sahrani (STKIP Subang, 2024)
This study aims to explore how horticultural activities can enhance the psychological well-being of the elderly through the PERMA model (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) developed by Martin Seligman. Using a qualitative method with a phenomenological approach, the study investigates the subjective experiences of elderly individuals who have been actively engaged in horticultural activities for at least six months. The findings reveal that horticultural activities provide benefits across the five dimensions of PERMA. Elderly participants reported increased positive emotions from the satisfaction of nurturing plants, full engagement in activities that induce flow experiences, strengthened social relationships through interactions with gardening communities, a sense of meaning in life through contributing to the environment, and personal accomplishments derived from caring for plants. Factors such as social support, the intensity of involvement, and the physical condition of the elderly significantly influence the effectiveness of horticultural activities. This research offers new insights into the importance of horticulture as an activity-based intervention to enhance the well-being of the elderly. Additionally, the results are expected to serve as a reference for developing community programs and policies that support the involvement of elderly individuals in meaningful activities.